Fast transformation algorithms of haar - Beletsky, A. Y.; Beletsky, A. A.; Davletyants, A. A. (Proceedings of National Aviation University (archive), 2003)
The below is the structure chart o f the tree for the direct and inverse discrete transformation o f thesignals on the finite interval in the basis o f the Haar functions that allow minimizing the resourceexpenditures fo r the software or hardware implementation o f the algorithm